2020
DOI: 10.1186/s12884-020-03168-4
|View full text |Cite
|
Sign up to set email alerts
|

Health may be compromised by social interactions depending on culture among postpartum Arab and Jewish Israeli women

Abstract: Background: Social support is generally perceived to facilitate health in postpartum women; however, previous research shows that this is not always true. Social interactions intended to provide support can be perceived as negative and in turn, may have negative impacts on maternal health. The purpose of the present study was to asses if social support and negative interactions at one month after childbirth can predict maternal health four months after childbirth, and if this relationship is influenced by cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Several studies exploring the potential negative effects of postpartum rituals provide support for these findings (Abudabbeh, 1998;Chien et al, 2006;Lincoln & Chae, 2012;Puddister et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Several studies exploring the potential negative effects of postpartum rituals provide support for these findings (Abudabbeh, 1998;Chien et al, 2006;Lincoln & Chae, 2012;Puddister et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…Other studies concur that a woman's relationship with her mother-in-law can have a major impact on postpartum health, affect mental and physical health, and even induce marital conflict (Ginja et al, 2018;Green et al, 2006;Heh et al, 2004). Puddister et al (2020) found that negative interactions predict health problems in postpartum women. In the current study, women often experienced physical aches as well as feelings of anger and stress brought on by constant customary visits that failed to achieve their well-intentioned goal.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, this specific investigation represents a cultural comparison that goes beyond the common east vs. west or WEIRD vs. non-WEIRD studies, which can shed light on additional sources of cultural differences and similarities in affect. A few cross-cultural studies that include Palestinian-Arab mothers were conducted in Israel, in which the population comprises a relatively individualistic Jewish society (74.4%) and a more collectivistic Palestinian-Arab society (20.9%) 97 . It was demonstrated that Palestinian-Arab parents better adapt to work following the first childbirth compared to Jewish parents, as infants were cared for by a family member 98 .…”
Section: Introductionmentioning
confidence: 99%